Crime and (Disparate) Punishment: the Eighth Circuit's Erroneous Application of the Categorical Approach in Bakor v. Barr - Emily Thieman (Washington University Journal of Law and Policy, 2022)
Consistent application of federal law has been an important policy consideration since the founding of the United States. However, the Eighth Circuit undermined this interest in Bakor v. Barr, when it held that, for immigration purposes, failing to register as a sex offender was categorically a crime involving moral turpitude. This ruling meant that the defendant was subject to the INA’s deportability grounds—an interpretation that stood in stark contrast to the conclusion of other circuits who interpreted similar state statutes. This Note argues that the Eighth Circuit’s ruling in Bakor was unprecedented and must be remedied under federal law. The author analyzes the relevant statutory provisions and subsequent circuit opinions to reveal why the analysis and interpretation in Bakor was inappropriate. The Note concludes with a question of whether and to what extent the decision in Bakor should be remedied by action from the Supreme Court.
Keywords: Bakor; Barr; Deportation; Statute; Eighth Circuit; Consistent; Application; Res judicata; Precedent; Unprecedented; Federal law; Supreme Court; Circuit opinion; Interpretation; Categorical; Crime; Moral; Turpitude